2020
DOI: 10.5194/acp-2019-1025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring wintertime regional haze in Northeast China: role of coal and biomass burning

Abstract: <p><strong>Abstract.</strong> As one of the intense anthropogenic emission regions across the relatively high latitude (> 40° N) areas on the Earth, Northeast China faces serious problem on regional haze during long winter with half a year. Aerosols in polluted haze in Northeast China are poorly understood compared with the haze in other regions of China such as North China Plain. Here, we for the first time integrated bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The results suggested that haze formation in this study might be affected by combustion sources. Cl À and Na + were mainly from industrial emissions and coal combustions (Zhang et al, 2017); K + can be from biomass and coal combustions (Zhang et al, 2020). The CCs of Cl À , Na + , K + with PM 2.5 were 0.83, 0.79, and 0.88, showing positive correlations.…”
Section: àmentioning
confidence: 96%
“…The results suggested that haze formation in this study might be affected by combustion sources. Cl À and Na + were mainly from industrial emissions and coal combustions (Zhang et al, 2017); K + can be from biomass and coal combustions (Zhang et al, 2020). The CCs of Cl À , Na + , K + with PM 2.5 were 0.83, 0.79, and 0.88, showing positive correlations.…”
Section: àmentioning
confidence: 96%